Three single-nucleotide polymorphisms in LPA account for most of the increase in lipoprotein(a) level elevation in African Americans compared with European Americans. Issue 12 (13th July 2006) - Chretien, J-P; Coresh, J; Berthier-Schaad, Y; Kao, W H L; Fink, N E; Klag, M J; Marcovina, S M; Giaculli, F; Smith, M W
Abstract : Background: The extent which universally common or population-specific alleles can explain between-population variations in phenotypes is unknown. The heritable coronary heart disease risk factor lipoprotein(a) (Lp(a)) level provides a useful case study of between-population variation, as the aetiology of twofold higher Lp(a) levels in African populations compared with non-African populations is unknown. Objective: To evaluate the association between LPA sequence variations and Lp(a) in European Americans and African Americans and to determine the extent to which LPA sequence variations can account for between-population variations in Lp(a). Methods: Serum Lp(a) and isoform measurements were examined in 534 European Americans and 249 African Americans from the Choices for Healthy Outcomes in Caring for End-Stage Renal Disease Study. In addition, 12 LPA variants were genotyped, including 8 previously reported LPA variants with a frequency of >2% in European Americans or African Americans, and four new variants. Results: Isoform-adjusted Lp(a) level was 2.23-fold higher among African Americans. Three single-nucleotide polymorphisms (SNPs) were independently associated with Lp(a) level (p<0.02 in both populations). The Lp(a)-increasing SNP (G-21A, which increases promoter activity) was more common in African Americans, whereas the Lp(a)-lowering SNPs (T3888P and G+1/inKIV-8A, which inhibit Lp(a) assembly) were more common in European Americans, but all had a frequency of <20% in one or both populations. Together, they reduced the isoform-adjusted African American Lp(a) increase from 2.23 to 1.37-fold(a 60% reduction) and the between-population Lp(a) variance from 5.5% to 0.5%. Conclusions: Multiple low-prevalence alleles in LPA can account for the large between-population difference in serum Lp(a) levels between European Americans and African Americans.